Apithological Inquiry: Learnings from an Ecological Aesthetic. (19th September 2013) - Varey, Will; Ing, David; Wilby, Jennifer
<x xml:space="preserve">Abstract</x> This paper extends contributions from the philosophy of ecological systems theory to frame new learnings in the practice of apithological inquiry. These learning insights are combined in levels of logical categories of types to inform the generative structuring of the observations of complex systems. Sets of choices in composition, coherence, constrictions and contributions are outlined. Observational errors comprising forms of naïve realism, entity reification, gross simplification, values projection and normative assertions are contextualized. The alternatives of ontological humility, epistemological openness, methodological appropriateness, axiological reflexivity and metonymic responsibility are proposed. The learning choices outlined are reflective of the practice by which an apithological aesthetic informs the appreciation of complex systems. From this analysis, five observational protocols are derived as requirements for the praxis of apithological inquiry. Copyright © 2013 John Wiley & Sons, Ltd.